Penerapan Algoritme Finite State Machine Berbasis Fragment Shader untuk Proses Pengambilan Keputusan pada Non Player Character (Studi Kasus Game Battle Tank) - Muhtadin Ziqi Maulana; Eriq Muh. Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Non player character (NPC) is a character in a game that is not controlled by players, but is controlled through computer programs made by humans. According to the gameAI model the NPC has the ability to make movements and decision making. The battle tank game that was developed by the author in this study also has an NPC developed. there is the game the researcher uses the finite state machine (FSM) algorithm in the decision making process of the NPC. But there is an idea about the application of the FSM algorithm that is by using a shader fragment. With the implementation of the FSM algorithm based on shader fragments, it is expected to get better performance. Because the process of the shader fragment is done in the graphics processing unit (GPU). So that the process carried out can be carried out in parallel between the decision making process and other processes. In applying FSM algorithms based on shader fragment requires three maps, namely world map, agent map and fsm map. After testing the effect of the number of NPCs using 1, 5, 10 and 15 NPCs, respectively, obtained an average yield of 147, 69, 24 and 1 FPS. Whereas for testing the effect of game map size using map sizes of 20x20, 30x30 and 40x40 in succession yielding an average value of 66, 61 and 60 FPS.